Please, Download the Instructions to Authors Here, and Read Carefully Before Submitting - Nko’o Amvene, Samuel (HEALTH SCIENCES AND DISEASE, 2024)
I. JOURNAL SCOPE Health Sciences and Disease, is a peer reviewed medical journal that covers all aspects of medicine, pharmacy, biomedical and health sciences, including public health and societal issues. It is an “online first” publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Our mission is to inform and educate all the health professionals and to promote constructive debate on health issues that matter in the management not only of diseases but of health as a whole. The HSD team is based in Yaounde (Cameroon). Acceptance of manuscripts is based on the originality, the quality of the work and validity of the evidence, the clarity of presentation, and the relevance to our readership. Publications are expected to be concise, well organized and clearly written. Authors submit a manuscript with the understanding that the manuscript (or its essential substance) has not been published other than as an abstract in any language or format and is not currently submitted elsewhere for print or electronic publication. Manuscripts must be submitted by one of the authors of the manuscript. The submitting author takes responsibility for the article during submission and peer review. II. MANUSCRIPT SUBMISSIONS The preferred way for submission is the online submission. Please, refer to the Health Sciences and Disease home page: http://hsd-fmsb.org. Otherwise, manuscripts can be addressed to hsdeditor3@gmail.com or nkooamvenes@gmail.com. Inquiries about manuscript status and preparation, as well as letters to the editor, should be directed to / Nko’o Amvene Samuel Editor-in-Chief. Health Sciences and Disease. Faculty of Medicine and Biomedical Sciences PO Box 1364, Yaoundé Cameroon. Email: nkooamvenes@gmail.com Fast track For authors with a login, manuscripts can be submitted directly to : http://www.hsd-fmsb.org/index.php/hsd/author/submit/1 Please, send a copy to the Editor in Chief and ask fast track. Special article processing charges may be required. III. EDITORIAL POLICIES HSD’s Publications Policy Committee follows the recommendations of the International Committee of Medical Journal Editors (ICMJE), the World Association of Medical Editors (WAME), and the Committee on Publication Ethics (COPE) for guidance on policies and procedures related to publication ethics. The policies for HSD have been adapted from those three advisory bodies and, where necessary, modified and tailored to meet the specific content, audiences, and aims of HSD. Manuscripts are initially checked by the editor in chief or section editor for identification of gross deficiencies. At this stage, the proposal may be rejected. After this initial screening, articles are sent to two-reviewers. The review process may take days to weeks to reach a decision. The duration from submission to publication may take one to six months (average: 2 months). So, the authors should avoid contacting the editorial office less than 6 weeks after the initial submission.